Hubungan Kemampuan Penalaran Dan Pemahaman Konsep Dengan Pemecahan Masalah Pada Materi Bangun Ruang Sisi Datar - Shujianto, Dwi Lian; Azmi, Syahrul; Tyaningsih, Ratna Yulis; Turmuzi, Muhammad (FKIP Universitas Mataram, 2024)
This study aims to determine the relationship of reasoning ability with problem solving ability, to determine the relationship of concept understanding ability with problem solving ability, and to determine the relationship of reasoning ability and concept understanding ability together to the ability to solve math problems of Class IX students of SMPN 1 Mataram academic year 2023/2024. This type of research is ex post facto. The population of this study all students of Class IX as many as 394 students. The sample in this study is Class IX-A with the determination of sampling using Purposive random sampling technique. Data collection techniques in this study using tests. This research instrument in the form of Reasoning Ability Test, concept comprehension ability test and math problem solving ability test of Class IX students of SMPN 1 Mataram. The results of data analysis of simple correlation and multiple correlations were obtained, there is a relationship of reasoning ability with problem solving ability of Class IX students of SMPN 1 Mataram with a coefficient of determination of 84.7%. Then for the ability to understand the concept with the ability to solve problems of students in Class IX SMPN 1 Mataram with a coefficient of determination of 83.5%. The results of data analysis also showed that there is a significant relationship between the relationship of reasoning ability and the ability to understand concepts together against the ability to solve math problems of Class IX students of SMPN 1 Mataram with a coefficient of determination of 92.6%.